KINETIC AND THERMODYNAMIC STUDIES OF PURIFIED PROTEIN ISOLATED FROM EUPHORBIA TIRUCALLI LATEX - Sharma, Tripti; Dash, Priyanka; Das, Debajyoti; Ghosh, Goutam (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Â Â The kinetic and thermodynamic parameters of an isolated protein from the latex of Euphorbia tirucalli were studied in this work. The isolated protein was named as Euphorbian T and was found to possess proteolytic activity through milk clotting and caseinolytic digestion process. The electrophoresis analysis of purified Euphorbian T was carried out using sodium dodecyl sulfate-polyacrylamide gel. The aminoacids of Euphorbian T were appeared in different bands of 36.5, 39, 44 and 50 Kda. The effect of pH, temperature, and concentration of substrate on proteolytic activity of Euphorbian T was examined. The maximum proteolytic activity of this protein was obtained at pH 6. The temperature t(max) for maximum activity range of the enzyme was found to be 65Â°C. The Kinetics parameters i.e., Km and Vmax of the purified protein with milk and caesin as substrate, were estimated using Lineweaverâ€“Burk plot and were found to be 4 mg/dl, 0.21 U/mg and 2 mg/dl, 1.03 U/mg, respectively. Thermodynamic constants i.e., activation energy (Ea), change in enthalpy (Î”H) and change in entropy (Î”S) and free energy changes (Î”G) of Euphorbian T for milk were calculated using Arrhenius plot and were found to be 1.58 kcal/mol, 1.54 kcal/mol, âˆ’10.46 cal mol/deg and 18.87 kcal/mol respectively, whereas with the substrate caesin, the activation energy (Ea), change in enthalpy (Î”H) and change in entropy (Î”S) and free energy changes (Î”G) were calculated as 1.12 kcal/mol, 1.08 kcal/mole, âˆ’16.24 cal mol/deg and 16.34 kcal/mol, respectively. Keywords: Euphorbia tirucalli, Euphorbian T, Milk clotting, Caseinolytic.